2017
DOI: 10.3389/fmicb.2017.00877
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces colonosanans sp. nov., A Novel Actinobacterium Isolated from Malaysia Mangrove Soil Exhibiting Antioxidative Activity and Cytotoxic Potential against Human Colon Cancer Cell Lines

Abstract: Streptomyces colonosanans MUSC 93JT, a novel strain isolated from mangrove forest soil located at Sarawak, Malaysia. The bacterium was noted to be Gram-positive and to form light yellow aerial and vivid yellow substrate mycelium on ISP 2 agar. The polyphasic approach was used to determine the taxonomy of strain MUSC 93JT and the strain showed a range of phylogenetic and chemotaxonomic properties consistent with those of the members of the genus Streptomyces. Phylogenetic and 16S rRNA gene sequence analysis ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
126
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(128 citation statements)
references
References 99 publications
(149 reference statements)
2
126
0
Order By: Relevance
“…From their study, it was shown that methanolic extracts from 3 bacterial species contained a number of pyrrolopyrazines and either one of these extracts were effective against batteries of pathogenic bacteria, cancer cell lines and neuroprotection models [108] . Given that past studies have highlighted the presence of compound (6) in microbial extract with antioxidant potentials [40,48,100] , further points to its likely role in inducing antioxidant effect.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…From their study, it was shown that methanolic extracts from 3 bacterial species contained a number of pyrrolopyrazines and either one of these extracts were effective against batteries of pathogenic bacteria, cancer cell lines and neuroprotection models [108] . Given that past studies have highlighted the presence of compound (6) in microbial extract with antioxidant potentials [40,48,100] , further points to its likely role in inducing antioxidant effect.…”
Section: Discussionmentioning
confidence: 96%
“…It has been suggested that understudied ecosystem hold Streptomyces species which can meet the growing demand of drug discovery and development industry [77] . Researchers who made an effort to study Streptomyces from less explored ecosystems such as mangrove forest were able to discover novel Streptomyces species and Streptomyces strains showing potent antioxidant activities [40,42,66,68,78,79] . dards for potential match.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were significant lower number of studies reported Streptomyces with anti-Vibrio activity from the terrestrial environments as compared to the much higher number of studies on the marine Streptomyces. The higher isolation rate of Streptomyces strains from marine environment could be due to the recent interest of researchers toward the marine natural products discovery as many novel bacteria genus and species with production of novel compounds have been identified from the marine environment [179][180][181] . In another context, these phenomena seem to imply that the resources which can be accessed easily had been exhausted as extensive studies on the terrestrial soil derived microorganisms were observed over the years.…”
Section: Studies Of Streptomyces With Anti-vibrio Activitymentioning
confidence: 99%
“…The genus Streptomyces within the order Actinomycetales has spectacular diversity in morphology, genomic size, genomic G+C content, and amount of coding sequences. Streptomyces bacteria are noted by their large and linearized chromosomes with approximately 8.5-12 Mb in size and high GC content of about 67-78% [3,9,13] . The large genome of Streptomyces could account for their ability to produce many secondary metabolites [14] .…”
Section: Introductionmentioning
confidence: 99%